2020
DOI: 10.3390/jcm9103223
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes in Women with Long-Duration Type 1 Diabetes—25 Years of Experience

Abstract: Aims: Our study aimed to examine the pregnancy outcomes (maternal and fetal) concerning different models of antenatal care across a period of over 25 years (1993–2018) in 459 women with type 1 diabetes. Data from patients with a history of the condition lasting at least 15 years were considered eligible for analysis. Methods: The study group was divided into three cohorts based on the different models of treatment used in Poznan University Hospital, Poland: 1993–2000 (cohort I, n = 91), 2001–2005 (cohort II, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…While the risk of LGA increased parallel to control pregnancies, the literature is equivocal on this outcome. While two studies reported increasing rates of LGA ( 21 , 41 ), another study found no change despite improving protocols and medication regimens between the nineties and early 2000s ( 42 ). To decrease macrosomia, proper glycemic control seems to be important especially in the first trimester along with proper weight control of participants ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the risk of LGA increased parallel to control pregnancies, the literature is equivocal on this outcome. While two studies reported increasing rates of LGA ( 21 , 41 ), another study found no change despite improving protocols and medication regimens between the nineties and early 2000s ( 42 ). To decrease macrosomia, proper glycemic control seems to be important especially in the first trimester along with proper weight control of participants ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal counseling including glucose level control and a "special antenatal care program" is required to achieve better perinatal and pregnancy outcomes [5]. Even the Prolonged duration of T1DM disease can negatively affect the neonatal outcome if not controlled [10]. Potential adverse effects of diabetes on pregnancy outcomes, the presence of diabetes-related complications, medicationrelated risks, effect of physiological changes of pregnancy on glycemic control, all of this should be discussed with the patients.…”
Section: Discussionmentioning
confidence: 99%
“…High glucose levels negatively affect vascular function and may mimic the early phase towards the development of diabetic vasculopathy. Diabetic vasculopathy is associated with PE, growth restriction and mostly iatrogenic preterm birth [ 25 ]. Prior studies show that GDM raises the risk of LGA (OR—1.8 (CI—1.7–1.8)), PE (OR—1.7 (CI—1.6–1.7)) and preterm birth (OR—1.3 (CI—1.3–1.4)) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%